Migration remittances socio-economic effects on households : Case study Morocco - Louh-Amoud, Hasnaa (2025)
The purpose of this study is to examine remittances as a treatment and calculate the likelihood that it will affect consumption and, in turn, poverty. This research is a survey based on the quantitative research method. The data was collected through the questionnaire that was designed on Google Forms. The data collection was carried out by using a convenience sampling technique and the collected dataset was based on 73 questionnaire responses from Moroccan migrants. The data analysis was conducted in Microsoft Excel. The data analysis included the frequency distribution and descriptive statistics. The results of the study indicated that the income of the families increased significantly after receiving remittances; their annual savings, investments, and consumption also increased significantly. The families of the migrants bought cars, houses, and property, initiated businesses, and also invested capital in the growth of their current businesses. The overall analysis indicates that the poverty of the migrants` families is eradicated after receiving the remittances, the children are provided the education, and the consumption increases, which means everyone in the family eats good food. Moreover, the results also indicated the increased expense of migrants` families on healthcare. Since remittances are important for the families of the migrants and are also important in boosting the economy of the recipient country; therefore the results of this research can potentially help in the policy development to encourage the migration of citizens abroad so that foreign currency can be brought in the country and its economy can be boosted.